Laparoscopic Sacrocolpopexy Plus Colporrhaphy With an Small Intestine Submucosa Graft Versus Total Pelvic Floor Reconstruction for Advanced Prolapse: A Retrospective Cohort Study - Wang, Junyan (Int Neurourol J, 2019)
PURPOSE: Transvaginal mesh (TVM) results in a greater anatomic cure but more complications. We aimed to compare laparoscopic sacrocolpopexy (LSC) plus colporrhaphy with the small intestine submucosa (SIS) graft versus TVM for advanced pelvic organ prolapse (POP). METHODS: Patients with advanced POP who underwent LSC plus colporrhaphy with the SIS graft or TVM at a center between September 2015 and November 2016 were studied. Anatomical outcomes were evaluated using POP quantification. Functional outcomes related to POP and sexual life were evaluated using the Pelvic Floor Distress Inventory (PFDI-20) and the Pelvic Organ Prolapse/Urinary Incontinence Sexual Function Questionnaire (PISQ-12). Data regarding surgical procedures and patient demographic variables were recorded. Chi-square and Student t -tests were used for 2 independent samples. RESULTS: A total of 76 patients were enrolled in this study with 26 patients in the LSC plus colporrhaphy with the SIS graft group (group A) and 50 patients with TVM group (group B). All patients in both groups demonstrated significant improvement in anatomical outcomes (P<0.05) after surgery. PFDI-20 scores were significantly improved 12 months after operation in both groups (P<0.001). PISQ-12 scores were significantly improved in patients after surgery, especially patients in group A (P<0.001). Mesh exposure occurred in both groups as follows: 8 patients (30.7%) in group A and 5 patients (10%) in group B. CONCLUSIONS: Even though both surgeries showed excellent results for subjective and objective outcomes, the use of an SIS graft might increase the exposure of polypropylene mesh. We do not recommend LSC plus colporrhaphy with the SIS graft for advanced multiple-compartments prolapse.